Hubungan Dukungan Tenaga Kesehatan terhadap Pemberian Exclusive Breastfeeding (EBF) pada Ibu Bekerja - Sutrisminah, Emi; Hudaya, Isna; Wahyuningsih, Wahyuningsih (Jurnal Kesehatan, 2022)
The success of Exclusive Breastfeeding is the first step for humans to get a healthy and prosperous life and supports the achievement of sustainable development programs or Sustainable Development Goals (SDGs) in 2030 in the health sector. In the preliminary survey at the Bangetayu Health Center, Genuk District, Semarang, January-March 2020 as many as 93 babies who visited the Bangetayu Health Center Semarang City, there were 14% of babies who were exclusively breastfeeding. In interviews with health workers in the nutrition department at the Bangetayu Health Center, mothers work very little to do exclusive breastfeeding. This study aims to determine the relationship between health personnel support for exclusive breastfeeding for working mothers in Kudu Village, Genuk District, Semarang. The design of this study used descriptive-analytic with a cross-sectional approach and statistical tests used the Chi-Square test. This research was conducted from December 2020 until January 2021. The sample was selected with a total sampling technique of 36 mothers. The results showed that mothers working as freelancers/side workers (41.7%) aged 21-35 years (83.3%) had high school education (66.7%) the majority were multiparous (63.9%). Based on the criteria of support for health professionals, emotional support (75%) is supportive, reward support (100%) is supportive, instrument support (60%) is less supportive and information support (67%) is less supportive, as many (52.8%) working mothers do not provide exclusive breastfeeding. In this study, the Ï-value was obtained at 0.001 (<0.05). There is a relationship between the support of health workers and exclusive breastfeeding for working mothers.